A DECADE OF RESEARCH ON ACADEMIC BOREDOM IN HIGHER EDUCATION (2015-2025): A SYSTEMATIC REVIEW - Ying , Huang1; Mat Said, Seriaznita (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
Academic boredom is a pervasive yet understudied academic emotion in higher education, with well-documented negative effects on student engagement, academic performance, and well-being. This systematic review synthesises empirical research published between 2015 and 2025 to trace the conceptual evolution, methodological approaches, antecedents, outcomes, and coping strategies related to academic boredom. Following PRISMA guidelines, 23 studies from Web of Science and Scopus-indexed databases were analysed. The findings point to a clear shift from unidimensional to multidimensional conceptualisations, while also revealing a continued predominance of cross-sectional designs despite the growing interest in intervention-based research. Cross-cultural differences emerge in both the antecedents and coping mechanisms, and the wide variation in measurement approaches poses challenges for comparability across studies. The predominance of undergraduate samples further limits the generalisability of existing findings to postgraduate and other professional learning contexts. Building on these patterns, this paper proposes a dynamic person-environment interaction model and argues for greater methodological coherence, including the use of validated measurement instruments, cross-cultural comparative designs, and more robust experimental or quasi-experimental approaches to strengthen causal claims. It further differentiates the mechanisms underlying major intervention types and shows that their effectiveness depends on contextual factors such as cultural background, individual characteristics, and disciplinary demands. The findings offer practical implications for educators and psychological counsellors to design more targeted, context-sensitive interventions aimed at reducing students’ academic boredom and enhancing their well-being in higher education.